Understanding the Solution-Making Ability of Senior High School Students in Solving Photosynthesis Problems - Viki Afifah Almualimah; Wirawan Fadly; Munkhmaral Tumennasan (Jurnal Penelitian Pendidikan IPA, 2024)
This study further explains the errors made by senior high school students when trying to solve photosynthesis problems. The method used in this research is descriptive qualitative, involving a sample of four senior high school students. The study results will be discussed with Polya's problem-solving procedure, which includes understanding, planning, execution, and checking. Errors at the comprehension stage are in understanding the relationship between photons and photosynthetic light reactions and in drawing genealogies. Errors in the planning stage, in making wrong assumptions or inaccuracies in interpreting those derived from the understanding stage. In addition, this study found errors in identifying chemical reactions in photosynthesis and errors in mathematical reasoning competence. The conclusion of this study shows the failure in making photosynthesis problem-solving solutions due to the interaction between the problem-solving phase and the student's general competence.